Serological and molecular investigation of the presence of West Nile Virus (WNV) among wild birds in Kuala Gula, Perak - Abas, Fatin Amirah (2018)
West Nile Virus (WNV) is an arthropod borne virus derived from Flaviviridae family which is zoonotic in nature. The virus is transmitted mostly by mosquitoes and wild birds act as the natural amplifying reservoir while mammals served as dead-end host. Previous study on the prevalence of WNV among companion birds in Selangor showed there was an exposure towards the virus which signified the vector of WNV is presence in Malaysia that contribute to the transmission of the virus. However, there is still no study conducted on the occurrence of WNV among wild birds in Malaysia. By considering the facts that wild bird is the main reservoir of the virus and their migration nature from north to south hemisphere or vice versa, therefore, this study aims to screen the presence of WNV antibody and antigen in Ardeidae (wild birds) in Kuala Gula Bird Sanctuary, Perak. Kuala Gula is considered as high risk area since it is one of the spot for the migratory bird to stop by temporarily and mosquitoes breeding area due to abundance of rice paddies fields ecosystem. Twenty Ardeidae juvenile and adult birds were obtained through convenience sampling. Serum and oropharyngeal swabs were collected and subjected to competitive ELISA (ID Screen ® West Nile Competitive Multi-species) and one step rt-PCR targeting highly conserved gene in between the capsid and pre-membrane protein, respectively. Based on the serological test, 2/20 samples were positive to the pr-E antigen. For molecular study, 5 samples were positive for WNV antigen. The positive results were sent for sequencing analysis and revealed 98-100% homologous to WNV strain from Italy, United State, Hungary, Russia and Greece. Interestingly, this region are located within the migratory bird flyways. As a conclusion, this study showed that Ardeidae family of wild birds in Malaysia were exposed and infected to WNV and evidence of WNV is circulating in the region is demonstrated.